Cold as ice - Mlynowski, Sarah (New York : Scholastic Press, 2014)
On their sixth trip through the magic mirror, Abby and Jonah find themselves in the story of the Snow Queen, a troubled character who chose power over family and friendship, and Abby has to free the children the Queen has under her spell--with the help of her new friend, a talking reindeer called Ralph, and a strange girl named Sharon.
410
Accelerated Reader AR
Keywords: Snow Queen (Fictitious character) -- Juvenile fiction; Fairy tales -- Adaptations -- Juvenile fiction; Magic mirrors -- Juvenile fiction; Reindeer -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Friendship -- Juvenile fiction